2023
DOI: 10.1088/2057-1976/acc661
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel hierarchical designs for skin graft simulants with high expansion potential

Abstract: Skin graft designs play an essential role in healing severe burn injuries. Split-thickness skin grafting (STSG) is one of the commonly used techniques for treating large burn injuries. In STSG, parallel cuts are projected onto a small portion of excised healthy skin for expansion and covering a larger burn area. To date, expansions reported for STSG are very low and insufficient to cover large burn areas. In this work, novel traditional and auxetic hierarchical cuts were designed on skin graft simulants, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…In another work, Han et al [12] studied the stretchability using conductorbased silver composite auxetic structures. Several other studies also showed that the hierarchical structures can generate very high expansions [21,22,[36][37][38]. Here, six different skin graft structures were designed on the two-layer skin graft with a length and width of 35 mm.…”
Section: Geometrical Modelingmentioning
confidence: 98%
See 2 more Smart Citations
“…In another work, Han et al [12] studied the stretchability using conductorbased silver composite auxetic structures. Several other studies also showed that the hierarchical structures can generate very high expansions [21,22,[36][37][38]. Here, six different skin graft structures were designed on the two-layer skin graft with a length and width of 35 mm.…”
Section: Geometrical Modelingmentioning
confidence: 98%
“…Here, six different skin graft structures were designed on the two-layer skin graft with a length and width of 35 mm. The dimensions of the designs were taken from the literature on hierarchical architectures which shows high expansions [21,22]. The selection of the specific length was based upon the ratios taken from the slit length and slit thickness.…”
Section: Geometrical Modelingmentioning
confidence: 99%
See 1 more Smart Citation